The Da Vinci codebreaker an easy-to-use fact checker - Garlow, James L. (Bethany House, 2006)
"An exposeÃÅ of the bestselling novel. Readers questioning The Da Vinci Code can 'fact check' with this book of terms, events, people and places"--Provided by publisher.